2019
DOI: 10.1159/000501236
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Neurogenesis in Conditions of Chronic Stress Induced by Sciatic Nerve Injury in the Rat

Abstract: The dentate gyrus of the hippocampus is the primary location of adult neurogenesis, which is affected by a variety of external and internal factors, including activity of surrounding glial cells. This study concerns alterations in hippocampal neurogenesis and changes in activity of both proinflammatory and neuroprotective microglia/macrophages after sciatic nerve injury in the rat. Here, we demonstrated that the chronic pain induced by a peripheral nerve injury manifests in the hippocampus by a decrease in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Correlation between abnormal expression of cytokines in the hippocampus and chronic pain-like behavior has been demonstrated in animal models [23, 71]. Reduced proliferation and neurogenesis in the hippocampus, along with an increase in proinflammatory cytokines (CD86+) and a reduction in neuroprotective (CD163+) microglia/ macrophages, indicates increased activity of microglia/macrophages, which may lead to the suppression of neurogenesis reported in chronic neuropathic pain [72]. Furthermore, the reduction in neurogenesis may be related to the increases in other hippocampal proinflammatory cytokines, such as TNF-α [47] and IL-1β [23, 71], following nerve injury.…”
Section: Proinflammatory Factors In the Hippocampus Following Chronic Pain And Depressionmentioning
confidence: 99%
“…Correlation between abnormal expression of cytokines in the hippocampus and chronic pain-like behavior has been demonstrated in animal models [23, 71]. Reduced proliferation and neurogenesis in the hippocampus, along with an increase in proinflammatory cytokines (CD86+) and a reduction in neuroprotective (CD163+) microglia/ macrophages, indicates increased activity of microglia/macrophages, which may lead to the suppression of neurogenesis reported in chronic neuropathic pain [72]. Furthermore, the reduction in neurogenesis may be related to the increases in other hippocampal proinflammatory cytokines, such as TNF-α [47] and IL-1β [23, 71], following nerve injury.…”
Section: Proinflammatory Factors In the Hippocampus Following Chronic Pain And Depressionmentioning
confidence: 99%
“…Regarding the effects of neuropathic pain on the hippocampal dentate gyrus, a recent study reported that the onset of neuropathic pain causes signs of pathological inflammation in the hippocampal dentate gyrus, leading to a decrease in neurogenesis with memory destruction, which leads to a decrease in DCX. 15 Furthermore, a lack of PROX1, which is required for the maintenance of intermediate nerve progenitor cells in adult neurogenesis, has been reported to lead to increased apoptosis of DCX-expressing cells and lack of neurogenesis in adults. 16 In this study, we investigated the effects of exercise on the expression of DCX, a neurogenic cell marker, and PROX1, which is required for the maintenance of intermediate progenitor cells in neurogenesis, in our CCI rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain caused by neuroma, as a result of amputation, does not progress to the point of working memory impairment, but strangulated peripheral nerve injury, resulting in neuropathic pain, has been reported to cause signs of pathological inflammation in the dentate gyrus of the hippocampus, leading to decreased neurogenesis, with memory destruction. 15 Prospero homeobox protein 1 (PROX1), a master transcription factor essential for lymphatic endothelial cell differentiation and cell function in the hippocampal dentate gyrus, is required for granule cell maturation in this brain region. PROX1 is required for maintenance of intermediate progenitor cells in adult neurogenesis; and lack of PROX1 leads to increased doublecortin (DCX) cell apoptosis and lack of neurogenesis in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-surface TMEM126A expression was found to increase after LPS induction in macrophages over 24 h, while CD137L expression decreased [ 22 , 23 ]. Recent studies have shown that expression of the hippocampal microglia 1 surface marker CD86+ and microglial activation increase when neuropathic pain is induced by chronic peripheral nerve injury [ 8 , 38 ]. In addition, expression levels of TLR4/NF- κ B signaling pathway-related proteins are upregulated in the hippocampus of neuropathic pain model mice [ 39 ].…”
Section: Discussionmentioning
confidence: 99%